Uncertainty and estimation in economics, vol. 3 - Champernowne, D. G. (Edinburgh : Oliver & Boyd ; San Francisco : Holden Day, 1969)
Volume 3 is concerned with the impact of uncertainty on various aspects of economic life. It discusses insurance and other precautions against disaster; choice in risky situations, for example in portfolio-selection; planning under uncertainty, whether by an individual planning his savings or the officials in a firm employing critical path analysis.
Includes bibliographical references and index.
rpm 27/10/2017
Loans
Keywords: Economics, Mathematical; Statistical decision